Shear Driven Deformation and Damage Mechanisms in High-performance Carbon Fibre-reinforced Thermoplastic and Thermoset Composites - Yazdani Nezhad, Hamed; Mills, Andrew R.; Hernandez, Thibault P. A. (Cranfield University, 2020)
The underpinning data related to monolithic and cyclic testing of thermoplastic and thermoset carbon fibre-reinforced polymer composites for description of shear driven deformation and damage mechanisms at micro-scale, related to high-performance aerospace grade structures undergoing high mechanical strains.
Keywords: 'CFRP composite'; 'PEEK'; 'Shear damage'; 'Plasticity'; 'High strain'; 'Fibre-matrix debonding'; 'Aerospace Engineering'; 'Aerospace Materials'; 'Aerospace Structures'; 'Composite and Hybrid Materials'